The Perinatal Grief Scale (33-item Short Version): validity and reliability of the Turkish - YILDIZ, HATİCE (CUMHURIYET UNIV TIP FAK PSIKIYATRI ANABILIM DALI, 2017)
Objective: This methodological study aimed to test the validity and reliability of the Turkish version of the Perinatal Grief Scale (33-item Short Version). Methods: The study included 185 women who were living perinatal loss and up to 12 weeks past. Data were collected using a questionnaire on sociodemographic features and the Turkish version of the Perinatal Grief Scale (33-item Short Version). Validity studies included language and content validity. For reliability analyses, Cronbach's alpha coefficients were calculated and, for test-retest reliability, the scale was re-administered after a two-week interval. Results: Content validity index of the scale was 0.95. The overall Cronbach's alpha coefficient was calculated as 0.96, ranging from 0.91 to 0.93 for three subscales. Item-total correlations were between 0.11 and 0.86. The overall test-retest reliability was 0.91. Conclusion: It was determined that the 32-item version is a valid and reliable instrument that can be used for living perinatal loss women evaluating grief in the Turkish population. The total score of perinatal grief and grief subscale score decreased with removaling of the article 12.
Keywords: perinatal loss; pregnancy; grief; scale; validity; reliability; PREGNANCY